The clinical efficacy of traditional Chinese medicine in the treatment of malignant pleural effusion: A protocol of systematic review and meta-analysis. Issue 39 (25th September 2020) - Lin, Zhen; Jiang, Mengyuan; Gao, Lirong; Zhang, Huachun
Abstract: Background: The objective of this meta-analysis was to summarize and identify the available evidence from studies to estimate the clinical value of traditional Chinese medicine (TCM) in the treatment of malignant pleural effusion (MPE). And provides clinicians with evidence on which to base their clinical decision making. Methods: This review will include all studies comparing clinical efficacy of TCM in the treatment of MPE. The search strategy will be performed in 9 databases. We will not establish any limitations to language and publication status, published from inception to the July, 2020. Two reviewers will screen, select studies, extract data, and assess quality independently. Outcome is clinical efficacy, QLQ-C30 questionnaire and safety. The methodological quality including the risk of bias of the included studies will be evaluated. We will carry out statistical analysis using RevMan 5.3 software. Results: This study will summarize current evidence to assess the efficacy and safety of TCM in the treatment of MPE. Conclusion: The findings of this study will provide helpful evidence for the clinician, and will promote further studies, as well as studying the value of TCM.